Development of Self-disinfecting Paints and In Vitro Assessment of their Cytotoxicity on Human Cells - Querido, Micaela (2022)
Abstract publicado em: Laboratory Animals. 2021;49(6):273. https://doi.org/10.1177/02611929211065919